BIOPROSPECT OF BACTERIAL FIBRINOLYTIC PROTEASE FROM BEKASAM OF LONGTAIL TUNA AS ANTITHROMBOTIC AGENT: LITERATURE REVIEW AND BIBLIOGRAPHY STUDY - Trianes, Juwy; Ethica, Stalis N.; Afriansyah, M. Ardi; Darmawati, Sri; Rahmani, Nanik; Zilda, Dewi S. (Quality : Jurnal Kesehatan, 2024)
Introduction:Cardiovascular disease (CVD) is the leading cause of death worldwide, with thrombosis being a significant risk factor. Fibrinolytic proteases have potential as antithrombotic agents and could be developed into CVD drugs. Indonesia's traditional fermented products, such as fish Bekasam, are rich in microorganisms, including fibrinolytic protease-producing bacteria, yet their potential for CVD treatment is underexplored. Fish paste in Indonesia serves as a protein source and a reservoir of bacterial diversity, which could aid in discovering new antithrombotic agents. Objective: This literature review examines research trends over the past decade on fibrinolytic protease-producing bacteria in traditional fermented products, with a focus on Bekasam made from Longtail Tuna. This fermented food is an alternative source for obtaining bacteria with antithrombotic properties. Methods: Data for this review were sourced from Google Scholar, PubMed, and the dimension.ai database, using the keyword "bacterial fibrinolytic protease" from 2015 to 2024. Visualization of global research trends was performed using VOS viewer software. Results: The review found a scarcity of studies on fibrinolytic proteases from Bekasam bacteria. Lactic acid bacteria involved in Bekasam fermentation possess proteolytic enzymes that degrade fish protein into peptides and amino acids, potentially offering antithrombotic properties. This suggests natural protease sources from traditional fermented foods have significant biomedical potential. Research on fibrinolytic protease-producing bacteria from Bekasam in Indonesia is limited and requires further development. Exploring these local fermented products could yield innovative sources for thrombosis treatment